Analisis Perhitungan Angka Kebutuhan Nyata Operasi dan Pemeliharaan Pada Daerah Irigasi Jejeruk - Suryo Handoyo; Erni Mulyandari; Ratih Nilam Sari (Syntax Corporation, 2023)
An analysis of the calculation of the Actual Needs for Operation and Maintenance (AKNOP) of an irrigation area is urgently needed to determine the amount of the budget that must be spent by the relevant agencies in terms of operating and maintaining the irrigation area. In general, three parameters are observed, namely the cost of managing the implementation of operations and maintenance, the cost of operating surface irrigation, and the cost of maintaining surface irrigation networks. The purpose of this study was to analyze the magnitude of the Real Operation and Maintenance Performance Figures (AKNOP) in the Jejeruk Irrigation Area. The research method used is to analyze the cost of the three parameters mentioned above. The results showed that the cost of AKNOP in the Jejeruk Irrigation Area was IDR 854,227,960.00 (Eight Hundred Fifty-Four Million Two Hundred Twenty-Seven Thousand Nine Hundred Sixty Rupiah).